Milk properties of ewes fed with soybean seeds and the sensory evaluation of the produced Roquefort type cheese - Zeola N.M.B.L.; Silva Sobrinho A.G.; Hatsumura C.T.; Borghi T.H.; Santana V.T.; Merlim F.A.; Viegas C.R. (The value chains of Mediterranean sheep and goat products. Organisation of the industry, marketing strategies, feeding and production systems, 2016)
The objectives of this research were to evaluate properties of milk from 1/2 Lacaune 1/2 Ile de France ewes fed diets, formulated according to their nutritional requirements, with (7 and 14%) and without soybean seeds, with further elaboration of Roquefort type cheese. Ewes were milked from the third to the 59th day postpartum, and milk samples were collected for quantitative and physico-chemical analysis and preparing Roquefort type cheese for subsequent sensory analysis. Milk production (443.61 mL/day), density (1.035 g/mL), acidity (19.33°D) and pH (6.41) were not affected by the inclusion of soybean seeds in feeding the ewes; in the days of evaluation, effects were observed in the pH of milk (6.35 at 42 and 56 days of lactation). The Roquefort type cheese had excellent acceptance by the panel (notes 7.6 for color, 7.5 for flavor, 8.4 for tenderness and 7.6 for overall acceptability. The milk from ewes fed the diet containing 7% of soybean seeds had the best yield for cheese production (18.03%). Adequate physico-chemical properties of milk and sensory in Roquefort type cheese were observed with inclusion of soybean seeds, which are a source of unsaturated fat that may be used for lactating ewes.
Joint Seminar of the Subnetworks on Nutrition and on Production Systems of the FAO-CIHEAM Network for Research and Development in Sheep and Goats, 2015/06/16-18, Montpellier (France)